2018
DOI: 10.1186/s12938-018-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive impairments in high fall risk older adults: the effect of mechanical calf vibration on postural balance

Abstract: BackgroundImpairments in proprioceptive mechanism with aging has been observed and associated with fall risk. The purpose of the current study was to assess proprioceptive deficits among high fall risk individuals in comparison with healthy participants, when postural performance was disturbed using low-frequency mechanical gastrocnemius vibratory stimulation.MethodsThree groups of participants were recruited: healthy young (n = 10; age = 23 ± 2 years), healthy elders (n = 10; age = 73 ± 3 years), and high fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…This may be because the falls risk group tended to implement the ankle strategy in response to proprioceptive signals (muscle spindles) to maintain balance. Additionally, this result conflicts with that of Toosizadeh et al who reported that the high falls risk groups showed larger hip sway in the eyes-closed condition than the healthy non-fall risk groups [12]. A reduced multisegmental strategy seems to lead to decreased postural robustness during vibratory stimulus at 30 Hz in the falls risk group with lumbar spondylosis [3,14,23,24].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This may be because the falls risk group tended to implement the ankle strategy in response to proprioceptive signals (muscle spindles) to maintain balance. Additionally, this result conflicts with that of Toosizadeh et al who reported that the high falls risk groups showed larger hip sway in the eyes-closed condition than the healthy non-fall risk groups [12]. A reduced multisegmental strategy seems to lead to decreased postural robustness during vibratory stimulus at 30 Hz in the falls risk group with lumbar spondylosis [3,14,23,24].…”
Section: Discussionmentioning
confidence: 58%
“…Toosizadeh et al reported larger hip sway when maintaining balance under vibratory stimulus in the high-falls risk group of elderly people than in the healthy group [12]. Accordingly, balance impairments, such as variability in postural control strategies and possibility of impaired proprioception, may also lead to an increased risk of falls among elderly people with lumbar spondylosis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have proven the effect of vibration therapy in preventing falls and fractures and in improving balancing ability in normal elderly [29,30]. Our previous randomized controlled trial with 710 healthy, active and independent postmenopausal women over 60 years old had shown LMHFV to have significant improvements in reducing falls, reaction time and movement velocity and in providing maximum excursion of balancing ability assessment as well as quadriceps muscle strength [15].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proven the effect of vibration therapy in preventing falls and fracture, and improving balancing ability in normal elderly (29,30). Our previous randomized controlled trial with 710 healthy, active and independent postmenopausal women over 60 years old had shown LMHFV to have significant improvements in reducing falls, reaction time, movement velocity, and maximum excursion of balancing ability assessment and also quadriceps muscle strength (15).…”
Section: Discussionmentioning
confidence: 99%